Anatomical Pathology and Histology of the Trachea and Lungs of Broiler Infected with Avibacterium paragallinarum - Rahmawati, Indra; Hidayah, Nurul; Wardhani, Lailia Dwi Kusuma (Universitas Bengkulu, 2023)
This case study aims to determine the causes of pathological changes in anatomy and histology in the trachea and lungs of the broiler. This study was taken from a broiler of Mr Alif Husbandry, who had clinical symptoms of clear discharge from sinuses, anorexia, conjunctivitis and difficulty breathing on July 5th 2022, in Gresik. The anatomical pathology and histological examination results showed changes in the trachea and lungs, showing hemorrhage and inflammatory cell infiltration. The results of microbiological examination from the sinus swab identified Avibacterium paragallinarum. In this study, clinical symptoms, anatomical pathology, and histology of the trachea and lungs of broiler chickens were caused by infection with Avibacterium paragallinarum.